Evolution and the psychology of thinking : the debate - Over, D. E., 1946- (Current issues in thinking & reasoning., 2003)
The field of evolutionary cognitive psychology has stimulated considerable interest and debate among cognitive psychologists and those working in related areas. In this collection, leading experts evaluate the status of this new field, providing a critical analysis of its most controversial hypotheses. These hypotheses have far reaching implications for cognition, including a modular view of the mind, which rejects, in its extreme form, any general learning or reasoning abilities. Some evolutionary psychologists have also proposed content-dependent accounts of conditional reasoning and probabi.